Loss of miR-143 and miR-145 in condyloma acuminatum promotes cellular proliferation and inhibits apoptosis by targeting NRAS - Liu, Xiaoyan (R Soc Open Sci, 2018)
The expression profile of miRNAs and their function in condyloma acuminatum (CA) remains unknown. In this study, we aimed to detect the effects of miR-143 and miR-145, the most downregulated in CA samples using high-throughput sequencing, on cell proliferation and apoptosis, to determine a novel therapeutic target for CA recurrence. RT-qPCR was used to validate the lower expression of miR-143 and miR-145 in a larger size of CA samples, and the expression of NRAS in CA samples was significantly higher than self-controls as determined by western blotting assay. Luciferase assay was performed to confirm that miR-143 or miR-145 targeted NRAS directly. Transduction of LV-pre-miR-143 or LV-pre-miR-145 to human papilloma virus (HPV)-infected SiHa cells led to reduced proliferation, greater apoptosis and inhibition of expression of NRAS, PI3 K p110α and p-AKT. However, knockout of miR-143 or miR-145 in human epidermal keratinocytes by delivery of CRISPR/CAS9-gRNA for target miRNAs protected cells from apoptosis and upregulated expression of target genes as described above. MiR-143 and miR-145 sensitized cells to nutlin-3a, a p53 activator and MDM2 antagonist, while their loss protected cells from the stress of nutlin-3a. Furthermore, siRNA targeting NRAS showed similar effects on proliferation and apoptosis as miR-143 or miR-145. Taken together, our results suggest that loss of miR-143 or miR-145 in CA protects HPV-infected cells from apoptosis induced by environmental stress, in addition to promoting cellular proliferation and inhibiting apoptosis by targeting NRAS/PI3 K/ATK. Restoration of miR-143 or miR-145 might provide an applicable and novel approach to block the recurrence and progression of CA.